The contribution of church leadership with the current church doctrines to minimize discrimination against people living with HIV/AIDS - Maqanda, Sipiwo Knowledge (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.